High ferritin in homozygous and heterozygous β-thalassemia tends to decrease oxidative stress levels - Maskoen, Ani Melani; Reniarti, Lelani; Sumantri, Nur Imaniati; Sahiratmadja, Edhyana (Universa Medicina, 2018)
BackgroundIneffective erythropoiesis and multiple blood transfusions may cause iron overload, leading to high level of ferritin in β-thalassemia patients. Iron has the ability to catalyze the production of reactive oxygen species (ROS), which can be prevented by an adequate activity of superoxide dismutase (SOD) and glutathione peroxidase (GPx). The aim of this study was to explore the association between high ferritin levels and oxidative stress among β-thalassemia patients by measuring SOD and GPx levels. MethodsThis was a cross sectional study among β-thalassemia major patients. Ferritin, SOD, and GPx were measured and compared between β-thalassemia patients with homozygous IVS1nt5 and heterozygous IVS1nt5/HbE mutations, which were the most prevalent mutations found in our previous study. The Spearman correlation test was used to analyze the data. ResultsThe ferritin levels in all β-thalassemia major patients were very high (range: 791-12,340 µg/L). However, no significant differences were observed (p=0.318) between homozygous IVS1nt5 (n=45) compared to heterozygous IVS1nt5/HbE (n=13). The oxidative stress markers SOD and GPx were not significantly different between homozygous IVS1nt5 and heterozygous IVS1nt5/HbE (p=0.450 and p=0.323, respectively). The correlations between ferritin and SOD and GPx oxidative stress levels were not significant in both homozygous IVS1nt5 and heterozygous IVS1nt5/HbE mutations. ConclusionHigh ferritin levels in β-thalassemia patients tend to decrease the GPx level in all thalassemia patients and SOD level in half of the patients, indicating that GPx and SOD may play a role in the occurrence of oxidative stress among thalassemia patients. The mechanism of oxidative stress in thalassemia needs to be further explored.